Preparation and Capacitance Properties of Graphene Quantum Dot/NiFe−Layered Double‐Hydroxide Nanocomposite. Issue 3 (17th December 2020) - Samuei, Sara; Rezvani, Zolfaghar; Shomali, Ashkan; Ülker, Emine; Karadaş, Ferdi
Abstract: A new composite from graphene quantum dots (GQDs) and NiFe layered double hydroxide was successfully prepared by the coprecipitation method under optimal conditions. The nanoparticles of the composite were analyzed by X‐ray diffraction (PXRD), Fourier transform infrared spectroscopy (FT‐IR), scanning electron microscopy (SEM), and thermal gravimetric analysis (TGA) to obtain the structure, composition and morphology information. Also, the electrochemical properties were investigated by cyclic voltammetry, galvanostatic charge/discharge measurements, and electrochemical impedance spectroscopy. The nanocomposite displays a specific capacitance of 712.7 F g −1 and excellent cycle life after 2500 cycles by applying 10 A g −1 of the current density in 1 M KOH electrolyte, which confirms that the nanocomposite has superb capacitance retention (∼94.8 %) and can be used as a capable supercapacitor. Furthermore, this study provides a desirable procedure for the preparation of novel nanocomposites based on graphene quantum dots, which can be used in energy storage/conversion devices. Abstract : In this research, a GQD/NiFe−LDH nanocomposite was prepared for the first time. Its physical properties have been studied, which confirm its successful formation. Finally, the electrochemical properties were investigated, and the results showed that the prepared nanocomposite could be used to provide supercapacitors.